Penentuan Aktivitas Spesifik Radionuklida dan Estimasi Laju Dosis Efektif Radiasi Gamma di Kawasan Wisata Bukit Nobita Kota Padang - Hasanah.Kr, Nurul; Milvita, Dian; Wahyudi, Wahyudi; Hidayat, Maulidia (Jurnal Fisika Unand, 2024)
Research has been carried out on determining the specific activity of radionuclides 226Ra (Radium), 232Th (Thorium), 40K (Kalium), and 137Cs (Cesium) in soil, water, and plant samples using a gamma spectrometer in the Bukit Nobita Tourism Area Padang City. This study shows the effective dose rate of gamma radiation received by tourists, tour managers, and farmers. Prepared soil, water, and plant samples were then measured using a gamma spectrometer. Gamma radiation dose rates were calculated 1 meter above the ground at 19 locations. The results showed that radionuclide 226Ra was only detected in soil samples, while radionuclides 232Th and 40K were detected in all samples except water samples. Radionuclide 137Cs were not detected in all samples. The specific activity of radionuclides is still below the threshold recommended by PERKA BAPETEN No.16 of 2013, which is 1000 Bq/kg for 226Ra and 232Th and 10000 Bq/kg for 40K. The specific activity of 137Cs radionuclide is still below the threshold recommended by PERKA BAPETEN No.16 of 2012, which is 100 Bq/kg. The effective dose rate received by tourist visitors, tour managers, and farmers is still below the threshold recommended by BAPETEN, which is one mSv/year.